"Not just bow and string and notes": Directors' perspectives on community building as pedagogy in Celtic traditional music education organizations. (November 2018) - Gilbert, Lisa
Celtic traditional musics, such as those originating in Ireland and Scotland, are typically transmitted outside formal avenues. Most studies regarding the learning of Celtic traditional music have focused on the experience of teachers and students, but less is known about the philosophies of organization directors who create contexts for teacher–student interactions. In an effort to fill this gap, this qualitative interview study examines the perspectives of nine directors of organizations located in Europe and North America dedicated to teaching Celtic traditional music. Analysis showed that directors perceived the aural transmission of the music as helping students connect with each other and build community. Further, directors' beliefs about history tended to motivate their decision-making processes toward fostering community as part of their pedagogical practice. The learning goals they set for students tended to emphasize these intangible goals over and above technique- or repertoire-related aims, with social skills being included in their definitions of "musicianship." Implications are raised regarding meaning-making and beliefs about history in Celtic traditional music communities.